Methods of conservative antibiotic treatment of acute uncomplicated appendicitis: A systematic review. Issue 4 (April 2019) - Talan, David A.; Saltzman, Darin J.; DeUgarte, Daniel A.; Moran, Gregory J.
Abstract : BACKGROUND: Meta-analyses and a recent guideline acknowledge that conservative management of uncomplicated appendicitis with antibiotics can be successful for patients who wish to avoid surgery. However, guidance as to specific management does not exist. METHODS: PUBMED and EMBASE search of trials describing methods of conservative treatment was conducted according to Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. RESULTS: Thirty-four studies involving 2, 944 antibiotic-treated participants were identified. The greatest experience with conservative treatment is in persons 5 to 50 years of age. In most trials, imaging was used to confirm localized appendicitis without evidence of abscess, phlegmon, or tumor. Antibiotics regimens were generally consistent with intra-abdominal infection treatment guidelines and used for a total of 7 to 10 days. Approaches ranged from 3-day hospitalization on parenteral agents to same-day hospital or ED discharge of stable patients with outpatient oral antibiotics. Minimum time allowed before response was evaluated varied from 8 to 72 hours. Although pain was a common criterion for nonresponse and appendectomy, analgesic regimens were poorly described. Trials differed in use of other response indicators, that is, white blood cell count, C-reactive protein, and reimaging. Diet ranged from restriction for 48 hours to as tolerated. Initial response rates were generally greater than 90% and most participants improved by 24 to 48 hours, with no related severe sepsis or deaths. In most studies, appendectomy was recommended for recurrence; however, in several, patients had antibiotic retreatment with success. CONCLUSION: While further investigation of conservative treatment is ongoing, patients considering this approach should be advised and managed according to study methods and related guidelines to promote informed shared decision-making and optimize their chance of similar outcomes as described in published trials. Future studies that address biases associated with enrollment and response evaluation, employ best-practice pain control and antibiotic selection, better define cancer risk, and explore longer time thresholds for response, minimized diet restriction and hospital stays, and antibiotic re-treatment will further our understanding of the potential effectiveness of conservative management. LEVEL OF EVIDENCE: Systematic review, level II.